Pilot assessment of an on-demand telehealth 'left without being seen' follow-up programme. (May 2023) - Sheridan, Matthew D; Adams, Katharine T; Booker, Ethan; Krevat, Seth A; Calabrese, Mary; Gomes, Kylie; Ratwani, Raj M
Introduction: On-demand telehealth can have a high rate of patients requesting visits and dropping off without being seen by a provider, especially during the COVID-19 pandemic. Methods: On-demand telehealth requests made to a large healthcare system in the USA between 15 March 2020 and 31 May 2020 were included for analysis with a focus on patients who were defined as left without being seen (LWBS). As part of a pilot program a registered nurse attempted to call LWBS patients within 24 hours of their telehealth request and asked if they were ok, if they sought care for their original visit reason, what that care was, or if they still needed guidance. This information and patient demographics were analyzed. Results: During the study period there were 21, 610 completed on-demand telehealth visits and 1852 patients for whom there were LWBS attempted follow-ups. Most patients LWBS for a reason that originated from the patient and not associated with the provider or telehealth platform. The mean wait time for LWBS patients was 12.4 min compared to patients waiting 15.1 min before engaging with a provider to complete a visit. Of the 1852 total LWBS patients in the follow-up programme, 819 (44.2%) were successfully contacted with a follow-up phone call. Most of these patients (63.2%) already completed or planned to complete a telehealth visit, 13.6% indicated they no longer needed to see a provider, and 12.8% planned or already completed an in-person visit. Only 2.2% went to an emergency department. Discussion: Results suggest patients can effectively self-manage their care needs.